Farm‐scale evaluation of herbicide band application integrated with inter‐row mechanical weeding for maize production in four European regions. (19th May 2016) - Vasileiadis, V P; van Dijk, W; Verschwele, A; Holb, I J; Vámos, A; Urek, G; Leskovšek, R; Furlan, L; Sattin, M
Summary: To promote integrated weed management (IWM) implementation in Europe, robust evidence on the sustainability of such tools and strategies is needed to motivate their adoption by stakeholders. This can only be achieved through assessing and validating them at real farm scale and using existing farm equipment, under diverse climatic and soil conditions representative of European agriculture. In 2013 and 2014, 12 on‐farm experiments (i.e. real field conditions on commercial farms, with natural weed flora) were conducted in four important European grain maize‐producing regions comparing the efficacy of herbicide band application integrated with inter‐row mechanical weeding as a potential IWM tool with the conventional broadcast herbicide application (CON) used by the farms. The IWM tools tested were as follows: (i) early post‐emergence herbicide band application combined with hoeing, followed by a second hoeing in southern Germany, (ii) early post‐emergence herbicide band application followed by hoeing in eastern Hungary and central Slovenia and (iii) pre‐emergence herbicide band application followed by hoeing in northern Italy. Herbicide band application integrated with hoeing provided good and partial weed control along and between maize rows respectively. No significant yield differences were detected between IWM and CON. IWM greatly reduced herbicide input and was economically sustainable over the duration of this study with no significant difference in gross margin compared with CON in all cases. This IWM tool could therefore be considered for implementation in European maize systems.